Permafrost Hydrology - Woo, Ming-ko (Springer Berlin Heidelberg : Imprint: Springer, 2012)
Permafrost Hydrology systematically elucidates the roles of seasonally and perennially frozen ground on the distribution, storage and flow of water. Cold regions of the World are subject to mounting development which significantly affects the physical environment. Climate change, natural or human-induced, reinforces the impacts. Knowledge of surface and ground water processes operating in permafrost terrain is fundamental to planning, management and conservation. This book is an indispensable reference for libraries and researchers, an information source for practitioners, and a valuable text for training the next generations of cold region scientists and engineers.